Evaluation of ceftazidime-avibactam resistance in clinical isolates of Enterobacterales from a large tertiary-care hospital, Italy, 2019-2023 - L. Calabrese; E. Willison; G. Codda; E. Costa; V. Di Pilato; A. Marchese (Microbiologia Medica)
Not available.